Sorting operational indicators of container terminals - Rodrigues, Thiago de Almeida; Silva, Brenda Siqueira da; Brunetti, Brunela Louvem; Pizzo, Julia Barbosa (Brazilian Journal of Production Engineering, 2023)
Seaports are well known as playing an important role in multimodal transport systems and international supply chains, requiring operational efficiency to deliver value for the customers. In order to ensure a high-level service, managing an organization based on performance indicators are essential for drive the operations toward the strategic plan. Container terminals are inserted in this context, where the management effort and financial resources should be balanced in order to achieve the best utility of the entire system. With that in mind, this research aims to establish the dimensions of the most relevant operational indicators of Brazilian container terminals by applying the Analytic Hierarchy Process (AHP) multi-criteria method, providing a set of indicators as reference for decision-makers. Toward this goal, we carried out a systematic review in Scopus databases, identifying 38 dimensions of operational indicators that were pairwise compared by managers that represented 7 Brazilian container terminals, responsible for handling 71% of Brazil's container throughput. This research has made practical and managerial contributions, ranking the operational indicators to aid decision-makers to manage container terminals toward their strategy.
Keywords: seaport; operational indicator; AHP